Experimental Investigation on Mechanical and Durability Properties of Concrete with Plastic Waste - N V Visweswara Sastry Dhara, V.; kumar. K, Sunil; Vimala. A, Dr. (International Journal of Engineering and Technology, 2018)
Industrial activities in India are associated with significant amounts of non – biodegradable solid waste and plastic waste. Plastic waste being prominent which is rarely recycled with as much as 40% left in landfill. Plastic waste is causing environmental pollution which is a major problem in the present era as the usage of plastic is growing day by day and it takes hundreds of years for plastic material to degrade. The plastic if burnt releases many toxic gases, which are very dangerous for health. So, there is an urgent need to recycle plastic waste so as to reduce the environmental impact. One possible way to minimize the plastic waste is to use plastic waste in concrete industry. Environmental concerns arising from the over dredging of sand have led to restriction on its extraction across India, a suitable environmental friendly alternative to sand must be found to match the huge demand in the concrete construction industry. To tackle both the issues plastic waste can be used in the concrete as the replacement of fine aggregate in known proportions. In this research work the fine aggregate has been replaced by two types of plastic waste, one is Low Density Polyethylene (LDPE) and second one is Polypropylene (PP) in varying proportions to find out the optimum content of plastic waste. The optimum content of plastic waste was determined by conducting tests on mechanical and durability properties. The mechanical test results shown that LDPE and PP plastic waste can be used in concrete mixtures up to 5% replacement level with fine aggregate. For this replacement level the durability property – Sulphate attack resistance was determined, results demonstrate the mass loss of specimens and compressive strength.